Efectos de acolchado térmico y abonos orgánicos en rendimiento de Brassica campestris L. (col china) var. Jade Crown en Zungarococha-Iquitos-2018 - Aspajo Villacorta, Arístides (2022)
The present investigation work was developed in the facilities of the Project of Teaching and Investigation Garden Agrostologico, located in the Km. 5,800 highway Iquitos-Nauta, between the towns of Zungarococha and Port Almond, District of San Juan of Miraflores, County of Maynas, Department of Loreto, the objective was to determine the influence of the organic payments and the padded ones thermal on the Agronomic Characteristics and Yield in the Cultivation of Brassica Campestris L. (Chinese Cabbage) var. Crown, the statistical design of blocks was used totally at random with factorial arrangement of 2x4, the treatments they were: Tea of White thermal Padded humus+; Tea of Black thermal humus+Acolchado; Humus White thermal lombriz+Acolchado; Humus Black thermal lombriz+Acolchado; White thermal Mantillo+Acolchado; Black thermal Mantillo+Acolchado; White thermal Gallinaza+Acolchado; Black thermal Gallinaza+Acolchado; being reached the conclusion: That if significant differences exist among the padded ones thermal and the organic payments to a (p <0.05); that the best organic payment presently work was him You of humus, with respect to the padded one, the white color showed better results in plant height, head perimeter, head diameter, head height and plant weight; while the padded black color demonstrated better results in number of basal leaves, head weight and yield.